A Necessary Role for Cyclin D2 Induction During Colon Cancer Progression Mediated by L1 - Saha, Arka; Gavert, Nancy; Brabletz, Thomas; Ben-Ze’ev, Avri (Cells, 2024)
The cell adhesion molecule L1CAM (L1), mainly known for its function in brain cells, is a Wnt/β-catenin signaling target gene in colorectal cancer (CRC) cells, where it promotes invasion and liver metastasis. We interrogated which genes are expressed at increased levels in human CRC tissue and induced in CRC cell lines overexpressing L1. We found increased cyclin D2 levels in CRC tissue and LS 174T and HCT 116 human CRC cells overexpressing L1. Increased cyclin D2 in CRC cells was associated with higher proliferation rates, faster motility, tumorigenesis, and liver metastasis. The suppression of cyclin D2 expression by shRNA to cyclin D2 blocked the increase in these cellular properties of L1-expressing cells. The overexpression of cyclin D2 in the absence of L1 also conferred tumorigenic properties similar to L1 expression. The pathways involved in the elevation of cyclin D2 by L1 include NF-κB, Akt, and β-catenin signaling but not the Erk pathway. We found that in a significant percentage of human CRC tissue samples, cyclin D2 is expressed at high levels in the nuclei of cancer cells. At the same time, the adjacent normal mucosa was negative for cyclin D2 staining. The results suggest that the increased cyclin D2 expression by L1 is required to induce proliferative, motile tumor development in CRC tissue and can serve as a diagnostic marker and a target for CRC therapy.
CRIS-Team Scopus Importer:2024-11-22
Keywords: colon cancer; cyclin D2; invasion and liver metastasis; L1